Efficacy of artesunate-amodiaquine and artemether-lumefantrine fixed-dose combinations for the treatment of uncomplicated Plasmodium falciparum malaria among children aged six to 59 months in Nimba County, Liberia: an open-label randomized non-inferiority trial. - Schramm, B; Valeh, P; Baudin, E; Mazinda, C; Smith, R; Pinoges, L; Dhorda, M; Boum, Y; Sundaygar, T; Zolia, Y; Jones, J; Comte, E; et al. (BioMed Central, 2013)
BACKGROUND: Prospective efficacy monitoring of anti-malarial treatments is imperative for timely detection of resistance development. The in vivo efficacy of artesunate-amodiaquine (ASAQ) fixed-dose combination (FDC) was compared to that of artemether-lumefantrine (AL) among children aged six to 59 months in Nimba County, Liberia, where Plasmodium falciparum malaria is endemic and efficacy data are scarce. METHODS: An open-label, randomized controlled non-inferiority trial compared the genotyping adjusted day 42 cure rates of ASAQ FDC (ASAQ Winthrop®) to AL (Coartem®) in 300 children aged six to 59 months with uncomplicated falciparum malaria. Inclusion was between December 2008 and May 2009. Randomization (1:1) was to a three-day observed oral regimen (ASAQ: once a day; AL: twice a day, given with fatty food). Day 7 desethylamodiaquine and lumefantrine blood-concentrations were also measured. RESULTS: The day 42 genotyping-adjusted cure rate estimates were 97.3% [95% CI: 91.6-99.1] for ASAQ and 94.2% [88.1-97.2] for AL (Kaplan-Meier survival estimates). The difference in day 42 cure rates was -3.1% [upper limit 95% CI: 1.2%]. These results were confirmed by observed proportion of patients cured at day 42 on the per-protocol population. Parasite clearance was 100% (ASAQ) and 99.3% (AL) on day 3. The probability to remain free of re-infection was 0.55 [95% CI: 0.46-0.63] (ASAQ) and 0.66 [0.57-0.73] (AL) (p = 0.017). CONCLUSIONS: Both ASAQ and AL were highly efficacious and ASAQ was non-inferior to AL. The proportion of patients with re-infection was high in both arms in this highly endemic setting. In 2010, ASAQ FDC was adopted as the first-line national treatment in Liberia. Continuous efficacy monitoring is recommended. TRIAL REGISTRATION: The protocols were registered with Current Controlled Trials, under the identifier numbers ISRCTN51688713, ISRCTN40020296.